Caracterização de resíduos sólidos de coleta seletiva em condomínios residenciais: estudo de caso em Vitória, ES - Bassani, Patricia Dornelas (2011)
The characterization, identification and quantification of solid waste is of great importance for the preparation of management plans of solid waste. The residential condominiums upright deserve emphasis in management, since they constitute an important source of solid waste generation in large scale. Thus, this study aimed to realize the physical characterization of solid waste from selective collection of residential condominiums upright the city of Vitoria - ES. Were performed surveys of data, the physical characterization of solid waste tests and evaluated the results with respect to participation, revenue from the sale of recyclable, the operability of the program and the reduction of waste going to landfill. The average per capita of dry waste was found to be 0.069 kg / person / day. Among the materials that had segregated the largest amount were the paper and the lesser WEEE. The paper showed a gravimetric percentage above the national average. The other materials were below average in the country. There was no default behavior in the generation of waste weekly, found no correlation between the lifetime of the selective collection and per capita observed. There was a high negative correlation between the per capita generation and the number of apartments in condominiums, suggesting that the largest number of households have difficulties in disseminating the selective collection in every room, leading to smaller rates of participation. The mean apparent specific weight observed for dry solid waste was 68.04 kg/m3 , with rejects, and 62.58 kg/m3 , without rejects. The IRMR obtained was 6.05%, which is considered "medium", and the percentage of participation estimated at 19.93%. The potential revenue generated from the sale of recyclable materials was more than 120 thousand reais a month, ensuring the economic sustainability of associations of collectors. It was found the possibility of adjustments in the frequency of collection to minimize service costs. The transfer of waste to associations of collectors could be increased by 293 times and has the potential to reduce by more than 5% of municipal waste sent to landfills.